Pengembangan Keterampilan Ekoliterasi Anak Usia Dini Melaui Program Bank Sampah Sekolah - Irma Rismayana; Heru Kurniawan (Edu Happiness: Jurnal Ilmiah Perkembangan Anak Usia Dini, 2026)
The number of natural disasters is one of the lessons that fostering awareness of protecting the environment needs to be done from an early age, so that children have awareness of the importance of protecting the environment and its impact in the future. The purpose of this study is to describe and analyze how to develop early childhood electroliteracy skills through the waste bank program. This research is a field research using a qualitative descriptive approach. Data collection was carried out by means of interviews, observations, and documentation. Data analysis is carried out by data reduction techniques, data presentation, verification and conclusion drawn. The results of this research show that the implementation of waste banks is carried out with 3Rs (Reduce, Reuse, Recycle) where children are actively involved in collecting, weighing, sorting, and processing used goods into learning media. The skills formed in children are the skills to distinguish inorganic waste, resource management, environmental care actions, and socio-ecological collaboration. Based on the waste bank activities carried out at PAUD Prima Sakinah Islamic School Bekasi City, it can be concluded that these activities can develop early childhood ecoliteracy skills. This research is focused on waste bank activities and in one school so the results cannot be generalized. In addition, the method used is qualitative so that the effectiveness of the program cannot be known for sure